The Ethics of "Choosing Wisely": The Use of Neuroimaging for Uncomplicated Headache. Issue 5 (May 2017) - Cote, David J.; Laws, Edward R.
Abstract : Abstract : The use of magnetic resonance imaging (MRI) for evaluation of headache remains excessive among physicians across many specialties according to both the American Headache Society and the American College of Radiology, despite recent attempts at limiting overuse of imaging and procedures. As part of the Choosing Wisely campaign, both of these organizations have explicitly recommended against imaging in patients with uncomplicated or typical migraine headaches. Yet, the practice nevertheless remains prevalent, with estimates ranging from 12.4% to 15.9% of patients with uncomplicated headache receiving MRI in outpatient practices. The low prevalence of serious pathological findings on imaging in patients who present without other indicative symptoms and the high cost of such exams necessitates a thorough evaluation of appropriate use of MRI for headache. Here, we debate the problematic use of MRI for uncomplicated headache and put forth a discussion of possible interventions that could promote more efficient use of imaging. Overuse of imaging has the potential to open a box that cannot readily be closed, and physicians upstream of surgical decision making must remain aware of the downstream effects of their clinical choices.